Efficient overall water splitting over a Mo(IV)-doped Co3O4/NC electrocatalyst. (11th June 2021) - Zhao, Xinran; Yin, Fengxiang; He, Xiaobo; Chen, Biaohua; Li, Guoru
Abstract: To meet the demand of producing hydrogen at low cost, a molybdenum (Mo)-doped cobalt oxide (Co3 O4 ) supported on nitrogen (N)-doped carbon (x%Mo–Co3 O4 /NC, where x% represents Mo/Co molar ratio) is developed as an efficient bifunctional electrocatalyst for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). This defect engineering strategy is realized by a facile urea oxidation method in nitrogen atmosphere. Through X-ray diffraction (XRD) refinement and other detailed characterizations, molybdenum ion (Mo 4+ ) is found to be doped into Co3 O4 by substituting cobalt ion (Co 2+ ) at tetrahedron site, while N is doped into carbon matrix simultaneously. 4%Mo–Co3 O4 /NC is the optimized sample to show the lowest overpotentials of 91 and 276 mV to deliver 10 mA cm −2 for HER and OER in 1 M potassium hydroxide solution (KOH), respectively. The overall water splitting cell 4%Mo–Co3 O4 /NC||4%Mo–Co3 O4 /NC displays a voltage of 1.62 V to deliver 10 mA cm −2 in 1 M KOH. The Mo 4+ dopant modulates the electronic structure of active cobalt ion (Co 3+ ) and boosts the water dissociation process during HER, while the increased amount of lattice oxygen and formation of pyridinic nitrogen due to Mo doping benefits the OER activity. Besides, the smaller grain size owing to Mo doping leads to higher electrochemically active surface area (ECSA) on 4%Mo–Co3 O4 /NC, resulting in its superior bifunctional catalytic activity. Highlights: Mo 4+ was doped into Co3 O4 by substituting Co 2+ at tetrahedron site. Mo 4+ dopant tuned electronic structure of Co 3+ and enhanced HER activity. The Mo doping boosted the formation of lattice O and pyridinic N as OER active sites. 4%Mo–Co3 O4 /NC showed η10 of 91 and 276 mV in 1 M KOH for HER and OER, respectively.